African Modernities and Mobilities : An Historical Ethnography of Kom, Cameroon, C. 1800-2008 - Nkwi, Walter Gam (Book collections on Project MUSE., 2015)
In this book Walter Gam Nkwi documents the complexities and nuances embedded in African modernities and mobilities which have been overlooked in historical discourses in Africa and Cameroon. Using an ethnographic historical approach and drawing on the intricacies of what it has meant to be and belong in Kom- an ethnic community in the Northwest Region of Cameroon - since 1800, he explores the discourses and practices of kfaang as central to any understanding of mobility and modernity in Kom, Cameroon and Africa at large. The book unveils the emic understanding of modernity through the history and ethnography of kfaang and its technologies and illustrates how these terminologies were conceived and perceived by the Kom people in their social and physical mobilities. It documents and analyzes the historical processes involved in bringing about and making kfaang a defining feature of everyday life in Kom and among Kom subjects.